Direct numerical simulation of free-surface and interfacial flow using the VOF method: cavitating bubble clouds and phase change - Malan, Leon (Department of Mechanical Engineering, 2018)
Direct Numerical Simulation of two-phase ow is used extensively for engineering research and fundamental fluid physics studies. This study is based on the Volume-Of-Fluid (VOF) method, originally created by Hirt and Nicols. This method has gained increased popularity, especially when geometric advection techniques are used coupled with a planar reconstruction of the interface. The focus of the first part of this work is to investigate the hydrodynamics of isothermal cavitation in large bubble clouds, which originated from a larger study of micro-spalling, conducted by the French CEA. A method to deal with volume-changing vapour cavities, or pores, was formulated and implemented in an existing code, PARIS. The ow is idealized by assuming an inviscid liquid, negligible thermal effects and vanishing vapour pressure. A novel investigation of bubble cloud interaction in an expanding liquid using Direct or Detailed Numerical Simulation is presented. The simulation results reveal a pore competition, which is characterised by the Weber number in the ow. In the second part of the study the governing equations are extended to describe incompressible ow with phase change. The description of the work commences with the derivation of the governing equations. Following this, a novel, geometric based, VOF solution method is proposed. In this method a novel way of advecting the VOF function is invented, which treats both mass and energy conservation in conservative form. New techniques include the advection of the interface in a discontinuous velocity field. The proposed algorithms are consistent and elegant, requiring minimal modifications to the existing code. Numerical experiments demonstrate accuracy, robustness and generality. This is viewed as a significant fundamental development in the use of VOF methods to model phase change.